Assessment of Genetic Variability for Yield and Yield-Contributing Traits in Groundnut (Arachis hypogaea L.) Genotypes - Abera Seboka Yami; Wosene Gebreselassie Abtew (Journal of Food Quality)
The present study was conducted to evaluate the genetic variability of yield and yield-contributing traits in groundnut genotypes. The experiment was conducted in a simple lattice design. ANOVA revealed significant differences among the genotypes. High PCV and GCV were recorded for most of the traits, indicating these characteristics could be used as selection indices. The kernel yield per ha was significantly positive for all traits except days to 50% flowering and maturity. High to moderate heritability, along with high to medium genetic advance was obtained for oil content, days to maturity, days to 50% flowering, plant height, shelling percentage, 100SW, number of mature pods per plant, kernel yield, seed weight per plant, and harvest index. The results of the cluster analysis of the tested groundnut genotypes were grouped into three major clusters. The highest intercluster distance D2 was recorded between clusters I and III at 1690.78, followed by clusters II and III at 1198.27. Principal component analysis resulted in four principal components with eigenvalues greater than one. The first four principal components explained 77.92% of the total variation. The existence of the highest intercluster distance indicates that there is variability, which creates an opportunity for improvement.